Predictive efficacy of waist-related indices for sarcopenic obesity incidence in Chinese older adults: a nationwide cohort study - Chen Zhang; Landan Xiao; Hao Lu; Huisheng Deng (BMC Geriatrics)
Abstract This study aimed to evaluate the predictive capacity of the Body Roundness Index (BRI), Abdominal Body Shape Index (ABSI), Waist-to-Weight Index (WWI), and Waist-to-Height Ratio (WHtR) for sarcopenic obesity (SO) incidence among older adults in China using data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS). The cohort included 3,919 participants aged 65 and older, with a mean follow-up of 2.79 years. Sarcopenic obesity was defined by low muscle mass and high body fat. Multivariate Cox proportional hazards regression models and Generalized Additive Models (GAMs) based on the Poisson distribution were used to assess the associations and predictive performance of these indices. After adjustment, BRI (HR: 1.037, 95% CI: 1.014, 1.060), ABSI (HR: 13.247, 95% CI: 1.677, 104.660), WWI (HR: 1.023, 95% CI: 1.006, 1.040), and WHtR (HR: 1.007, 95% CI: 1.003, 1.010) were significant predictors of SO incidence. Threshold effect analyses revealed non-linear relationships for BRI and WHtR. The predictive model based on GAMs demonstrated strong discrimination (C-index: 0.879 for the modeling set and 0.876 for the validation set) and good clinical utility. These findings highlight the importance of early intervention for individuals with abdominal obesity to prevent future sarcopenic obesity, thereby reducing disease and social burdens and improving the quality of life for the elderly.